Resocialisation of Recovering Drug Addicts – Social, Spatial, and Architectural Aspects of Treating Drug Addicts - Janja Štibernik; Alenka Fikfak (Igra Ustvarjalnosti, 2018)
During treatment, drug addicts change their environment. The new environment and surroundings must adequately simulate and encourage the factors that positively affect their treatment, living (social, spiritual), learning, and work. The focus of this paper is the impact of the environment on the success of rehabilitation and (re)socialisation of drug addicts. Nowadays, setting foot in such an institution means an “immediate” removal from the established, everyday social environment as well as the virtual world. However, the provision of appropriate spontaneous and planned contacts with family and friends is necessary for an addict. Despite the removed social competence, it is important for an addict to settle down and strengthen the sense of belonging to a social environment. Meeting people and developing contacts with people from near and far is necessary to maintain social relationships during “isolation”, as this eases their resocialisation in their environment after the completion of treatment. This paper is based on the findings of semi-structured interviews and qualitative analysis of the answers received, case studies of spatial developments based on a qualitative design of social space, and various comparisons between domestic and foreign practices in view of the evaluation of spatial values. In the Results section, we present an applicative case of architectural composition of an ecovillage for rehabilitation of drug addicts based on social competence: development of an individual’s abilities for an independent functioning in a social environment.